Welfare effects of the euro cash changeover - Wunder, Christoph; Schwarze, Johannes; Krug, Gerhard; Herzog, Bodo (Bonn, 2006)
"Using merged data from the British Household Panel Survey (BHPS) and the German Socio-Economic Panel (SOEP), this paper applies a parametric difference-in-differences approach to assess the real effects of the introduction of the euro on subjective well-being. A complementary nonparametric approach is also used to analyze the impact of difficulties with the new currency on well-being. The results indicate a severe loss in well-being associated with the introduction of the new currency, with the predicted probability that a person is contented with his/her household income diminishing by 9.7 percentage points. We calculate a compensating income variation of approximately one-third. That is, an increase in postgovernment household income of more than 30% is needed to compensate for the rather drastic decline in well-being. The reasons for the negative impact are threefold. First, perceived inflation overestimates the real increase in prices resulting in suboptimal consumption decisions. Second, money illusion causes a false assessment of the budget constraint. Third, individuals have to bear the costs from the conversion and the adjustment to the new currency. Moreover, it is thought that losses are smaller when financial ability is higher. However, the impact of difficulties in using and converting the new currency is rather small, and the initial problems were overcome within one year of the introduction of euro cash."